The Effect of Collaterallizable Assets, Growth in Net Assets, Liquidity, Leverage and Profitability on Dividend Policy (Case Studies on Non-Financial Services Sector Companies Listed on the Indonesia Stock Exchange for the 2016-2019 Period) - Febrilia Izza Mauris; Nora Amelda Rizal (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Dividend policy is one of the most important functions for corporate finance and has influence with various company stakeholders. Dividend policy reflects the quality and reputation of the company, namely the company's ability to manage its business processes to generate profits well or vice versa. In practice, companies experience difficulties in determining and deciding dividend policies, namely the decision to withhold profits to be used as company operational development or to distribute dividends to shareholders to increase investor confidence in the company. The difference in interests that occurs in dividend policy is called agency theory. This study aims to determine the effect of collateralizable assets (COLLAS), growth in net assets, liquidity (CR), leverage (DER), and profitabilitas (ROE) on dividend policy (DPR) in non-financial service companies listed on the Indonesia Stock Exchange in 2016-2019. The data used in this study was obtained from financial report data taken from the official website of the Indonesia Stock Exchange. The population in this study are non-financial service companies listed on the Indonesia Stock Exchange in 2016-2019. The sampling technique used is perposive sampling and obtained 31 firms with a research period of 4 years, thus obtaining 124 sample data. The method of data analysis in this study is panel data regression analysis using software Eviews 11.0. The results showed that simultaneous collateralizable assets (COLLAS), growth in net assets, liquidity (CR), leverage (DER), and profitabilitas (ROE) had a significant effect on dividend policy (DPR). Meanwhile, partially Collateralizable Assets (COLLAS) has a significant effect in a positive direction on dividend policy. Growth In Net Assets has no significant effect in a negative direction on dividend policy. Liquidity (CR) does not have a significant negative effect on dividend policy. Leverage (DER) does not have a significant negative effect on dividend policy. Profitability (ROE) has a significant effect in a positive direction on dividend policy.